Visual Target Strategies in Infantile Nystagmus Patients With Horizontal Jerk Waveform - Imai, Takao; Takimoto, Yasumitsu; Okumura, Tomoko; Higashi-Shingai, Kayoko; Takeda, Noriaki; Kitamura, Koji; Kalubi, Bukasa; Fujikado, Takashi; Hirota, Masakazu; Midoh, Yoshihiro; Nakamae, Koji; Inohara, Hidenori (Frontiers in Neurology, 2018)
The aim of this study was to propose a new pathophysiological hypothesis for involuntary eye oscillation in infantile nystagmus (IN): patients with IN exhibit impaired gaze fixation, horizontal smooth pursuit and optokinetic nystagmus (OKN) and use saccadic eye movements for these underlying impairments. In order to induce saccades, they make enough angle between gaze and target by precedent exponential slow eye movements. IN consists of the alternate appearance of the saccade and the slow eye movements. Unlike most previous theories, IN is therefore considered a necessary strategy allowing for better vision and not an obstacle to clear vision. In five patients with IN, eye movements were analyzed during the smooth pursuit test, saccadic eye movement test, OKN test and vestibulo-ocular reflex (VOR) test. Their gaze fixation, horizontal smooth pursuit, OKN and the last half of the slow phase of VOR were impaired. The lines obtained by connection of the end eye positions of fast phase of nystagmus coincided with the trajectories of targets. The findings indicate that patients followed the target by the fast but not the slow phase of nystagmus, which supports our hypothesis. By setting the direction of slow phase of nystagmus opposite to the direction of the OKN stimulation, enough angle can be effectively made between the gaze and target for the induction of saccade. This is the mechanism of reversed OKN response. In darkness and when eyes are closed, IN weakens because there is no visual target and neither the saccade for catching up the target or slow phase for induction of the saccade is needed.